Spatial Modelling Analysis for Potential Expansion of Cipanas City Candidate Area as Autonomous City - Lili Somantri (Forum Geografi, 2024)
The establishment of new autonomous city is considered a significant decision and the proposal has been under review in Cipanas for several years. Therefore, this research aimed to address the proposal by conducting spatial modelling analysis for potential expansion of Cipanas as autonomous city, using Geographic Information System (GIS) method. The physical and social factors were analysed, using spatial overlay analysis to determine potential development area. SWOT analysis was also performed for qualitative insights into strengths, weaknesses, opportunities, and threats of the prospective Cipanas area. The results showed that Cipanas had significant potential to become autonomous city, with a particular focus on agriculture and tourism due to the varied topography and predominant natural land use. Through overlay analysis, areas in Pacet, Cipanas, and a small part of Cugenang Sub-districts were identified as potential development zones for the capital city. In general, Cipanas area was found suitable for the development of a major city with an agropolitan concept. Certain areas were considered more appropriate with urban characteristics compared to other areas based on specific criteria. Based on the results, recommendations include infrastructure improvements, economic sector diversification, tourism promotion, and disaster risk reduction activities. GIS spatial analysis facilitated the accurate identification of potential areas, aiding in mapping and pinpointing optimal areas for the establishment of new autonomous city.